The Role of the Gakkum Unit in Resolving Traffic Accident Cases Using Restorative Justice at the Malang Police Traffic Unit - Fauzi, Anang Dwi (Police Studies Review, 2024)
These accidents often have legal consequences and warrant criminal liability, demonstrating that strong law enforcement and infrastructure development are necessary to meet increasing transportation needs. This research explores the role of the Gakkum Unit at Malang Police in using restorative justice to resolve traffic accident cases. Using qualitative methods, this study deepens understanding of the application of restorative justice in the context of traffic law, highlighting how this approach facilitates justice, reconciliation and healing of relationships between perpetrators and victims. The findings show that the Gakkum Unit plays a vital role in promoting a more humane and inclusive approach in dealing with traffic accidents. In this research, factors that support and hinder the implementation of restorative justice are identified, providing an overview of the challenges and potential that exist in the current traffic law enforcement system. This research proposes recommendations for increasing the effectiveness of restorative justice, including increasing training, resources, and public awareness of the benefits of this approach. It is hoped that these recommendations will support traffic law enforcement reforms that are fairer and more responsive to community needs.